The Role Of Financial Mediator In Securities Trading On The Algeria Stock Exchange - Amina, Chenaa; Bey Khadija, Yahya; Nadia, Lakli (International Journal of Psychosocial Rehabilitation, 2022)
The study relates to a legal treatment of the role of the financial intermediary in the operations of trading securities on the Algiers Stock Exchange, as the Algerian legislator approved a legal system that frames the provisions of the financial intermediary in the operations of trading securities (movable values) that highlight its importance in the operations of the stock exchange. Legislative Decree No. 93-10 related to the MVC, amended and supplemented by Law No. 03-04 of February 17, 2003, is one of the texts that dealt with the issue of intermediaries, whereby the activity of the broker is practiced in the stock exchange operations after the approval of the Committee for the Organization of Exchange Operations and its control by the party. Commercial companies that are established specifically for this purpose, banks and financial institutions (Article 6 of Legislative Decree No. 10-9 relating to the Movable Values Exchange, amended and supplemented by Law No. 04-03 above). The legislature has authorized the financial intermediary to exercise all functions and operations in the movable values market, such as negotiating about Values transferred to his account and to the account of his customers, operations of buying and selling the transferred values to his account or to the account of others, managing the portfolios of transferred values to the account of others under a power of attorney, carrying out the liquidation endeavor. Accordingly, and in order to address the subject of study, it is necessary to search for conditions for acquiring and accrediting the status of a mediator in stock exchange operations on the one hand and the tasks entrusted to him in stock exchange operations by searching for the various works granted to him on the other hand. Based on the aforementioned, it has been completed. Relying on the descriptive and analytical approach in order to extract the role played by the financial intermediary in view of the legislative development that the legal system of the financial intermediary defined in the operations of trading securities on the Algiers Stock Exchange